Glycerol hyperhydration improves cycle time trial performance in hot humid conditions - Hitchins, S.; Martin, D. T.; Burke, L.; Yates, K.; Fallon, K.; Hahn, A.; Dobson, G. P. (European Journal of Applied Physiology, 1999)
Data indicate that the glycerol-induced performance increase did not result from plasma volume expansion and subsequently lower core temperature or lower cardiac frequencies at a given power output as previously proposed. However, during the glycerol trial, subjects maintained a higher power output without increased perception of effort or thermal strain.